Association between occlusal supports and nutritional status in older adults: A systematic review - Risako Mikami; Yuriko Komagamine; Norio Aoyama; Koji Mizutani; Yoshiyuki Sasaki; Takanori Iwata; Shunsuke Minakuchi; Manabu Kanazawa (Elsevier, 2024)
Background/purpose: Impaired masticatory performance results in nutritional deficiencies in older adults. This systematic review aims to investigate the following clinical question (CQ): Do occlusal supports impact nutritional intake or nutritional status in older individuals? Materials and methods: An extensive systematic literature search was performed to summarize the currently available knowledge to address the CQ. The cohort and intervention studies with participants of ≧60 years old or a mean age of 65 years performed before May 2021 were included. Studies were required to measure the parameters related to occluding tooth pairs/occlusal units and food/nutrient intake and/or nutritional status. Bias risk was assessed using the Risk of Bias Assessment Tool for Nonrandomized Studies. Results: After an independent screening of 1130 initial records, 24 reports from 22 studies were included. Participants (n = 8684) in the included studies were mainly residents of nursing homes or community-dwelling individuals. Following the assessment of bias risk, it is revealed that all studies had methodological weaknesses. Over half of the studies concluded that there was an association between occlusal support and nutritional intake or status. However, it was also revealed that various confounding factors are involved in the association between occlusal support and nutrition. Conclusion: This systematic review concludes that occlusal support might be associated with nutritional intake or nutritional status in the older population, although there are methodological limitations of each study. The evidence is still insufficient, and more well-designed studies are required.